A meta‐analysis of research on digital game‐based science learning. (27th February 2020) - Tsai, Yu‐Ling; Tsai, Chin‐Chung
Abstract: This meta‐analysis investigates the relative effectiveness of game‐based science learning against other instructional methods (Gameplay design) as well as against science game variants enriched with mechanisms (Game‐mechanism design). An overall medium effect size for Gameplay design ( k = 14, N es = 14, gRE = 0.646, p = .000), and an overall small‐to‐medium effect size for Game‐mechanism design ( k = 12, N es = 13, adjusted gRE = 0.270, p = .001) are reported. Further, the results of subgroup analyses suggest that students across educational levels all significantly benefit from game‐based science learning although there is no significant difference between the subgroup mean effects. Further, learning and gaming mechanisms play equal roles significantly increasing students' scientific knowledge gains. With these promising results, however, high variance within the subgroups of educational levels and those of gaming mechanisms indicate that gaming mechanisms should be developed with care to meet students' different needs in different educational levels. Lay Description: What is already known about this topic: Students prefer digital game‐based science learning to conventional instructions in science classroom settings. Students' scientific content knowledge/concept gains have been the focus of science education as well as game‐based science learning. The effects of game‐based science learning on students' scientific content knowledge/concept gains have been diverse. What this paper adds: Comparing to conventional science instructions, game‐based science learning produces an overall medium effect size on students' scientific knowledge achievement. Game‐based science learning significantly enhances students' scientific knowledge acquisition across all educational levels. Game mechanisms added have an overall small‐to‐medium effect on students' scientific knowledge achievement. Learning mechanisms and gaming mechanisms in science games play equal roles enhancing students' scientific knowledge acquisition. Gaming mechanisms should be designed with care. Implications for practice and/or policy: This study provides policy makers the empirical evidence supporting the pedagogical capacity of game‐based science learning for students' science knowledge acquisition comparing to mere conventional instructions. When developing gaming mechanisms in science games, educational game developers should be cautious with students' needs in different educational levels.